2010
DOI: 10.1161/circresaha.109.215228
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased S -Nitrosylation of Tissue Transglutaminase Contributes to Age-Related Increases in Vascular Stiffness

Abstract: Rationale: Although an age-related decrease in NO bioavailability contributes to vascular stiffness, the underlying molecular mechanisms remain incompletely understood. We hypothesize that NO constrains the activity of the matrix crosslinking enzyme tissue transglutaminase (TG2) via S-nitrosylation in young vessels, a process that is reversed in aging. Objective: We sought to determine whether endothelium-dependent NO regulates TG2 activity by S-nitrosylation and whether this contributes to age-related vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(147 citation statements)
references
References 38 publications
8
137
2
Order By: Relevance
“…Interestingly, the ER␤-selective agonist diarylproprionitrile induces S-nitrosylation proteins as a cardioprotective mechanism in the heart (49). Loss of S-nitrosylated proteins with age could ostensibly contribute to a loss of cardioprotective effects of E2 in older patients (50). Moreover, S-nitrosylation of interaction partners mediated through ER␤ could result in the characteristic "chain" patterns observed in the 2D-DIGE experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the ER␤-selective agonist diarylproprionitrile induces S-nitrosylation proteins as a cardioprotective mechanism in the heart (49). Loss of S-nitrosylated proteins with age could ostensibly contribute to a loss of cardioprotective effects of E2 in older patients (50). Moreover, S-nitrosylation of interaction partners mediated through ER␤ could result in the characteristic "chain" patterns observed in the 2D-DIGE experiments.…”
Section: Discussionmentioning
confidence: 99%
“…At cellular level, it has been shown that decreased nitric oxide (NO) bioavailability plays and important role in age-related vascular stiffness. Indeed, TG2 extracellular secretion and crosslinking activity are inhibited by S-nitrosylation, a post-translational modification of the cysteine residues in TG2 active site, by NO (Santhanam et al, 2010;Melino et al, 1997). Decreases in NO in arteria of old rats results to decreased TG2 S-nitrosylation, increased TG2 in the vascular matrix, and increased TG2 crosslinking function (Santhanam et al, 2010;Steppan et al, 2014).…”
Section: Transglutaminase 2 In Angiogenesis and Age-related Vascular mentioning
confidence: 99%
“…The diversity of regulatory mechanisms for SNO might account for the ability of SNO to regulate a variety of cellular conditions. Indeed, studies have implicated regulation by SNO in sex-specific protein changes (13,81,110), aging (95,97), cardiovascular disease (5,36,58,59,85,107,109), and renal function (113), to name a few.…”
Section: Reactivitymentioning
confidence: 99%